Breast masses in childhood: a single-center experience - Temuroğlu, Aytül; Aksoy, Gökalp Rüstem; Özşen, Mine; Gürpınar, Arif Nuri; Sevinir, Betül Berrin (Frontiers in Pediatrics, 2026)
ObjectivePediatric breast masses are rare conditions. Although most of them are benign, they can cause concern in families. The present study aims to determine breast masses’ clinical and pathological outcomes in childhood.Material and methodThe records of patients who underwent further evaluations for breast masses between 2010 and 2023 at a single center were retrospectively reviewed.ResultsA total of 32 patients with breast tumors were included in the study. The median age of the patients was 16 years (1-18 years); 90.6% (n = 29) were female, and 9.4% (n = 3) were male. Most patients, 90.6% (n = 29), had a painless, palpable mass. A family history of breast cancer was present in four patients. One patient had received chemotherapy for neuroblastoma and one for teratoma. The most common location was the upper outer quadrant in 35.5% of patients (n = 11). Bilateral mass involvement was present in five patients (15.6%). The mean tumor size was 32.64 ± 17.4 mm (range 9–80 mm). The mean tumor diameter was 24.6 ± 14.2 mm in patients who were followed without surgery and 39.2 ± 17.4 mm in those who underwent surgery (P = 0.017). A biopsy was performed in 53.1% (n = 17) of the patients, and surgery in 56.2% (n = 18). The most frequent pathology was fibroepithelial lesion and fibroadenomas 57.1% (n = 20). Malignant tumors (leiomyosarcoma and T cell lymphoma) were observed in 6.3% of the patients (n = 2) and borderline phyllodes tumors in 18.7% (n = 6). Recurrence was observed in 18.7% of the patients (n = 6) during the follow-up.ConclusionIn childhood, the most commonly encountered breast tumors are benign. However, careful monitoring is crucial due to the potential occurrence of malignant tumors. Further evaluations should be undertaken in patients with a history of malignancy or radiotherapy, masses larger than 5 cm, or masses with progressive growth.